2021
DOI: 10.1128/mbio.02397-21
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk between ARF1 and RhoA Coordinates the Formation of Cytoskeletal Scaffolds during Chlamydia Infection

Abstract: Chlamydia trachomatis is a major cause of human disease worldwide. The ability of Chlamydia to establish infection and cause disease depends on the maintenance of its parasitic niche, called the inclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…At ~32 to 40 hpi, actin scaffolds are woven around the inclusion to maintain its integrity as it expands ( 8 ). We and others have shown that the chlamydial effector InaC/CT813 is required for forming PTM-MT and actin scaffolds during C. trachomatis infection ( 9 11 ). Blocking actin scaffold formation by knocking out InaC or using actin-depolymerizing agents results in the premature lysis of inclusions ( 8 , 11 ), highlighting their role in Chlamydia development.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…At ~32 to 40 hpi, actin scaffolds are woven around the inclusion to maintain its integrity as it expands ( 8 ). We and others have shown that the chlamydial effector InaC/CT813 is required for forming PTM-MT and actin scaffolds during C. trachomatis infection ( 9 11 ). Blocking actin scaffold formation by knocking out InaC or using actin-depolymerizing agents results in the premature lysis of inclusions ( 8 , 11 ), highlighting their role in Chlamydia development.…”
Section: Introductionmentioning
confidence: 94%
“…We and others have shown that the chlamydial effector InaC/CT813 is required for forming PTM-MT and actin scaffolds during C. trachomatis infection ( 9 11 ). Blocking actin scaffold formation by knocking out InaC or using actin-depolymerizing agents results in the premature lysis of inclusions ( 8 , 11 ), highlighting their role in Chlamydia development. Recently, we found that InaC controls the formation of actin scaffolds by activating the small host GTPase RhoA ( 8 , 11 ).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…CpoS deficiency had a particularly detrimental effect on bacterial replication, as it resulted in a premature death of the infected cell, presumably as a result of premature inclusion lysis [ 40 , 41 ]. Interestingly, inclusion instability was also noted in cells infected with various other Inc mutants [ 40 ], including such deficient for InaC, an Inc that promotes microtubule stabilization and actin cage formation at the periphery of the inclusion [ 52 , 67 , 68 ]. Finally, concerning Chlamydia exit from host cells, we learned that the Incs MrcA and CT228 regulate myosin II motor protein activity to promote or suppress exit by extrusion [ 69 , 70 ], while the secreted protease CPAF and the plasmid-encoded factor PGP4 contribute to bacterial egress by host cell lysis [ 71 ].…”
Section: What Has the Application Of Genetic Tools Taught Us So Far A...mentioning
confidence: 99%
“…modify the membrane of their vacuole by secreting a class of effector proteins (Incs) that are inserted into the inclusion membrane (Bannantine et al, 2000). Incs interact extensively with host proteins and with each other (Gauliard et al, 2015, Mirrashidi et al, 2015), thus mediating a range of processes, such as homotypic fusion of inclusions (Hackstadt et al, 1999), formation of ER-inclusion contact sites (Derre et al, 2011), cytoskeletal rearrangements (Dumoux et al, 2015, Haines et al, 2021, Kokes et al, 2015), and modulation of host vesicular transport (Delevoye et al, 2008, Rzomp et al, 2006). The high number of Incs encoded by Chlamydia genomes, over 50 in C. trachomatis (> 5% of its protein-coding genes) (Weber et al, 2015), highlights their biological importance.…”
Section: Introductionmentioning
confidence: 99%